Contributions to the winter stoneflies (Plecoptera: Taeniopterygidae & Capniidae) of China - Shen, Ting; Cao, Jinjun; Li, Weihai; Bozdoğan, Hakan (Zootaxa, 2021)
A complementary re-description of Kyphopteryx dorsalis Kimmins, 1947 is presented on the basis of a fresh male and additional females from southeastern Tibet, southwestern China. The hitherto unknown inner structures of the female terminalia are described, as well as further details of the male genitalia. In this study, we also present the first records of Capnia s.l. yunnana Li & Yang, 2011 from Tibet and a formal description of an unassociated Capnia s.l. female collected together with the above species. An updated checklist of the named species of Capniidae and Taeniopterygidae from China is also given.